Exercise training: A hero that can fight two pandemics at once - Rodrigues Teixeira de Castro, R.; Giffoni da Silveira Neto, J.; Rodrigues Teixeira de Castro, R. (International Journal of Cardiovascular Sciences, 2020)
Government measures that restrict people at home during the COVID-19 pandemic do not need to encourage the wider spread of the sedentarism pandemic. Exercise can fight both public health problems, as long as it is adequately prescribed. Maintaining regular physical activity at home is pivotal for healthy living during and after the COVID-19 global crisis.